Cultural Shifts And Social Impacts Of Coffee Shops On Millennials: Pergeseran Budaya Dan Dampak Sosial Coffee Shop Pada Generasi Milenial - Daman Sudarman (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
The cultural and lifestyle shifts occurring in modern society, particularly among the millennial generation, have had a significant impact on the emergence and popularity of coffee shops. This research aims to analyze the transformation in coffee culture and the social impact of coffee shops on millennials. The method used in this study is library research.The results indicate that coffee shops have become iconic symbols of the millennial lifestyle, offering a comfortable and visually appealing environment for this generation. Millennials often choose coffee shops as gathering places, workspaces, or spaces to relax. Coffee shops have also become hubs for social activities and connections among individuals, enabling more direct social interactions compared to online platforms. This phenomenon has created a unique social and cultural atmosphere surrounding coffee shops, which in turn impacts the local economy. Furthermore, changes in millennials' lifestyles have influenced their self-perception and consumption patterns. Coffee shops serve as venues where they can express themselves, seek new experiences, and cultivate their identities. Millennials utilize coffee shops as platforms to showcase their lifestyles and aspirations, as well as to gain social recognition and prestige.